Partnership with the private sector as a mechanism to activate the role of municipalities in local economic development in Algeria - LARGUET , Soumia; ABBASSI , Siham (Journal of Human Sciences, 2025)
Algeria has recently witnessed new economic trends, particularly regarding the search for new economic alternatives to meet the requirements of economic development. This study examines how the existing partnership between the public sector, represented by municipalities, and the private sector can contribute to achieving local economic development in light of the new economic orientation of the Algerian state. The study relied on descriptive and analytical approaches, and concluded that the approach of partnership between municipalities and the private sector is among the successful approaches to local economic development. However, it is not expected to play the developmental role desired in the short term, given its new shortcomings, which require the adoption of innovative mechanisms and new legislative amendments to overcome them. Digitization can also be adopted as a tool to develop models for partnerships between the two sectors.